History of cytopathology and the origins of Papanicolaou - Romero, Nery (2001)
Leopold Koss, in the 3rd edition of his book "Diagnostic Cytology and its histopathologic bases" indicates that cytology is "the art and science of interpreting the human body cells, are peeling exfoliated epithelial surfaces or obtained of different tissues by various methods "(1). The history of cytology, in our view, is closely related to the emergence of two great creations, the microscope and the definition of cell.